(untitled) (MAUSAM, 1972)
A mathematical method is developed to calcalate the value of any parameter at a grid-point from its average values over three squares symmetric around the point. The weighting functions are derived from the dimensions of the scanning squares. This procedure takes into account all differentials below the sixth order in a Taylor expansion. Truncation error due to neglect of higher order differentials is assessed. Certain refinements to the weighting functions due to using finite number of observations in scanning squares are introduced. Modification and suppression of small waves are discussed in relation to scan-length, average distance between observatories and their random distribution. The method was tried on long and short waves by a numerical experiment.